Peroxidase - antiperoxidase unlabelled antibody technique (PAP) for the detection of hepatitis B surface antigen in hepatic tissue - Alves, Venâncio Avancini Ferreira (1980)
Peroxidase - antiperoxidase unlabelled antibody technique onhepatic tissue sections was carried out for detection of hepatitis B surface antigen. This method demonstrated advantages over immunofluorescence, regardíng to its utilization in fixed 01' in block tissue, in routíne procedures, in optical or electronic microscopy, for visuaJization of detailed morphological tissue structures by selective staining and preparation of permanent records. This technique using ali of the immunological materiaIs prepared in our laboratory at Instituto Adolfo Lutz, São Paulo, Brazil, is an impor tan t step for its suitabiJity for use in diagnostic procedures.